Nye åkre og gamle funn Metodiske betraktninger om undersundersøøkelser av skelser av søørrøøstnorske steinalderbostnorske steinalderbo--plasser i dyrket mark - Alex Mjærum (Primitive Tider, 2021)
Old finds in new plough soils – Excavations of infield Stone Age sites in Southeastern Norway. This paper discusses the results of field archaeology in southeast Norway in the last ten years and concludes that infield Stone Age sites are rarely excavated in this region. Although the reasons are complex, this can partly be explained by the emphasis given to other types of sites and subjects, and is also related to the lack of a disciplinary tradition of survey and excavation of plough zone sites. The article also examines the value of infield Stone Age sites and presents and evaluates some of the methods used in recent excavations of plough soil settlements. Although some of these sites can provide new information about settlement patterns and the Stone Age economy, there are also sites that are of less interest. An important conclusion is that more focus should be given to the more productive sites both by applying new methods of survey and by excavations.